Computational modeling of the dynamics of sexual transmission of HIV/AIDS through cellular automats (Cell-DEVS) - Pino Romero, Neisser (2018)
In the present research article, a computational model is developed by means of cellular automatas (Cell-DEVS) that describes the transmission dynamics of HIV / AIDS in a closed group of heterosexual people who are sexually active. From the perspective of the mathematical epidemiology we have the mathematical model SI of W. O. Kermack and A. G. McKendrick that represents the dynamics of the sexually transmitted disease by means of the ordinary differential equations. Wherecomputational simulations will be carried out both by numerical methods and cellular automatas to analyze the evolution of the disease over time, and how the results obtained can be interpreted to generate adequate intervention activities as part of public politics.